Copper-Catalyzed Thiolation Cyclization of 1-Chloro-1,5-enynes with Sodium Hydrosulfide: Synthesis of CF3-Containing 1H-Isothiochromenes - Shi, Shuai; Sun, Lei-Lei; Liao, Zhi-Yong; Zhang, Xing-Guo (Synthesis, 2012)
A copper-catalyzed regio- and stereoselective 6-exo-dig cyclization of 1-chloro-1,5-enynes with sodium hydrosulfide has been developed. In the presence of copper(I) iodide and sodium tert-butoxide, a variety of (Z)-1-methylene-3-(trifluoromethyl)-1H-isothiochromenes were prepared in moderate to good yields via thiolation cyclization of 1-alkynyl-2-(2-chloro-3,3,3-trifluoroprop-1-enyl)benzenes with sodium hydrosulfide.
Keywords: copper; thiolation; 6-exo-dig cyclization; 1H-isothiochromenes; sodium hydrosulfide